Investigating the Onboarding Process for Interns in Software Development: An Initial Survey - Moraes, Riordan; Araújo, Allysson Allex; Rivero, Luis; Viana, Davi (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2024)
The onboarding process is important for successfully integrating new workers into software development teams. Specifically for interns, this process can be even more relevant, as it is their first professional contact. Thus, it is relevant to investigate how onboarding occurs and how possible techniques are being applied to provide more adequate guidance for interns in the software industry. This paper aims to analyze the onboarding process for interns in the software development context. The initial study was conducted through an initial survey with 53 interns, observing the main elements and onboarding techniques used in their previous experiences. As an emerging result, mentoring, intern documentation, and social interaction were highlighted as the most promising techniques for successful onboarding, according to the participants. Furthermore, we identified that effective onboarding contributes to building a positive organizational culture and talent retention. Regarding the contributions, we cover the participants’ perceptions of techniques and challenges faced in intern onboarding in software development. Our future work involves surveying individuals responsible for supervising trainees or interns in the context of software development companies.